2017
DOI: 10.1155/2017/9795806
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Approach to Facilitate Fracture Healing: Topical Chinese Herbal Paste with Oral Strontium Ranelate

Abstract: Strontium ranelate (SrR) is one of the pharmaceutical agents reported to be effective on the promotion of fracture healing. This study aimed to evaluate the integrative effect of the oral SrR with a topical Chinese herbal paste, namely, CDR, on facilitation of bone healing. The in vivo efficacy was evaluated using rats with tibial fracture. They were treated with either CDR topically, or SrR orally, or their combined treatments. The in vivo results illustrated a significant additive effect of CDR on SrR in inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 42 publications
(44 reference statements)
0
8
0
Order By: Relevance
“…Modern researches proved that the traditional Chinese medicine for promoting blood circulation and removing blood stasis accelerates bone fracture healing by improving blood rheology, accelerating angiogenesis in injured areas and improving blood circulation at the injured site [13][14][15][16]. Bone healing usually requires four steps: blood vessel nonunion (breakage), proliferation of vascular endothelial cells (VEC), VEC moving buds, and three-dimensional structure reconstruction of the lumen [21,22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Modern researches proved that the traditional Chinese medicine for promoting blood circulation and removing blood stasis accelerates bone fracture healing by improving blood rheology, accelerating angiogenesis in injured areas and improving blood circulation at the injured site [13][14][15][16]. Bone healing usually requires four steps: blood vessel nonunion (breakage), proliferation of vascular endothelial cells (VEC), VEC moving buds, and three-dimensional structure reconstruction of the lumen [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…Many basic studies have shown that HIF-1α cell-associated signaling pathway is closely related to microangiogenesis in osteogenesis [11,12]. Traditional Chinese medicine for promoting blood circulation and removing blood stasis can improve local and systemic blood circulation in the early stage of fracture healing, improve local blood oxygen status, and create a good internal environment for fracture healing [13][14][15][16]. The traditional Chinese medicines such as Taohong Siwu (TSW) Decoction for promoting blood circulation and removing blood stasis are used to treat orthopedic diseases [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Considering that the topical administration of the DAEP herbal paste has not been studied before, it was prepared by mixing the four extracts at their simplest ratio 1:1:1:1 (in dry weight). Two percent of borneol (w/w) was added to increase the transdermal ability of the paste [19].…”
Section: Methodsmentioning
confidence: 99%
“…ey are beneficial to the local and systemic blood circulation during the early stages of fracture healing, which may improve local blood oxygen status and create a good internal environment for fracture healing [17][18][19][20]. Taohong Siwu (TSW) decoction is one of the most popular TCM for promoting blood circulation, removing blood stasis, and treating orthopedic diseases [21,22].…”
Section: Introductionmentioning
confidence: 99%